The Role of Banks Where Service Replication Has Eroded Institutional Franchises - Richard Aspinwall (Levy Economics Institute of Bard College, 1991)
Over the past decade forces of competition and adverse economic conditions–combined with regulatory forbearance and the moral hazards generated thereby-have contributed to severe erosion of bank profitability and a mounting number of insolvencies. At least three implications of this erosion may be identified. First, in response to pressures on capital and profits bank business strategies have begun emphasizing contraction and consolidation. Second, barring new elements of weakness afflicting other suppliers of financial services on which banks could capitalize, the role of banks in the future is likely to be reduced further. Third, the extent of this reduction will hinge to a considerable degree on whether new public policies applying to capital and deposit insurance are imposed. Life support policies will not restore the weak, but will impair the competitive viability of those remaining strong. The material is divided into four parts. The first consists of a brief summary of recent bank performance. The succeeding sections address the three implications introduced above.
Keywords: 330